2014
DOI: 10.1007/s11999-014-3537-6
|View full text |Cite
|
Sign up to set email alerts
|

Are There Risk Factors for Complications of Perforator-based Propeller Flaps for Lower-extremity Reconstruction?

Abstract: Level IV, therapeutic study. See the Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 29 publications
5
77
2
6
Order By: Relevance
“…In Lazzeri et al's [43] review, propeller perforator flaps for trunk and upper limb reconstruction resulted in the total complication rate of approximately 13.8 %, with a major complication rate of 3.4 %. However, the complication rate is higher in the lower extremities than in the other parts of the body, with frequent venous congestion and partial flap necrosis, and the total flap failure rate has been reported to be 1.1-5.6 % in the lower extremities [42,44,45]. In our study, age, sex, and comorbidities, including diabetes mellitus, hypertension, coronary artery disease, were similarly distributed between the two groups.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In Lazzeri et al's [43] review, propeller perforator flaps for trunk and upper limb reconstruction resulted in the total complication rate of approximately 13.8 %, with a major complication rate of 3.4 %. However, the complication rate is higher in the lower extremities than in the other parts of the body, with frequent venous congestion and partial flap necrosis, and the total flap failure rate has been reported to be 1.1-5.6 % in the lower extremities [42,44,45]. In our study, age, sex, and comorbidities, including diabetes mellitus, hypertension, coronary artery disease, were similarly distributed between the two groups.…”
Section: Discussionsupporting
confidence: 49%
“…Vega et al studied free transverse rectus abdominis muscle flaps (TRAM) in breast reconstruction and found that smoking, obesity, and radiotherapy correlated to the incidence of complications [41]. Regarding pedicle flaps, Innocenti et al [42] studied the risk factors for complications with the use of propeller flaps in lower extremity reconstruction and found no specific risk factors for complications; however, there are potential risk factors for complications with the use of perforator-based fasciocutaneous flaps. In Lazzeri et al's [43] review, propeller perforator flaps for trunk and upper limb reconstruction resulted in the total complication rate of approximately 13.8 %, with a major complication rate of 3.4 %.…”
Section: Discussionmentioning
confidence: 99%
“…El avance en los conocimientos de la anatomía vascular y la circulación cutánea ha posibilitado el desarrollo de una gran variedad de colgajos pediculados y perforantes. [11][12][13][14][15][16] El colgajo paraescapular ha probado ser versátil, robusto y confiable. Cuando es utilizado para cubrir defectos en extremidades severamente lesionadas permite reemplazar defectos fasciocutáneos con tejido similar al perdido.…”
Section: Discussionunclassified
“…[5][6][7] en esta serie, el uso del colgajo fasciocutáneo sural de base distal nos permitió cubrir con éxito 20 defectos de tejidos blandos que afectaban la tibia distal, el tobillo y el pie, tanto en reconstrucciones postraumáticas como en defectos secundarios a resecciones oncológicas.…”
Section: Discussionunclassified